EVALUASI KINERJA WAKTU DAN BIAYA PADA PROYEK WU TOWER BANDUNG - Utomo, Bagus Krido; Kusmana, Dody (Sistem Infrastruktur Teknik Sipil (SIMTEKS), 2024)
The research evaluates the time and cost performance of the Wu Tower Project in Bandung using the Earned Value (EV) method. The scope of the research includes a comprehensive literature study on the concept of Earned Value (EV) and its application in the evaluation of time and cost performance of construction projects. In addition, the research also includes the measurement of the actual time and cost performance of the Wu Tower Project using the EV method, analysis of influencing factors, especially those related to design complexity, scope changes, and labor, as well as comparison of actual time and cost performance with predetermined standards. The performance of the project implementation time in the 1st month (one) to the 8th month (eight) is progressing well as indicated by the SV (Schedule Variant) variant value is positive or the SPI performance index ≥ 1, this indicates that the work is progressing both in schedule and budget. For the 9th (ninth) to 11th (eleventh) month, the SV (Schedule Variant) value is negative, which means that the work is delayed, but the project completion expenditure budget is still quite efficient because the SPI value is ≥ 1. Based on the Performance Index value, the overall SPI value gets an average value of 1.73, which means that the project is progressing towards time performance, while the CPI value generally gets an average SPI value ≥ 1, which means that the costs incurred are more economical, so that the project is more efficient.